Whole Exome Sequencing in Children With Type 1 Diabetes Before Age 6 Years Reveals Insights Into Disease Heterogeneity - Andreia Fiúza Ribeiro; Ana Laura Fitas; Marcela Oliveira Pires; Paula Matoso; Dário Ligeiro; Daniel Sobral; Carlos Penha-Gonçalves; Jocelyne Demengeot; Íris Caramalho; Catarina Limbert (Journal of Diabetes Research, 2024)
Conclusions: WES found potentially deleterious rare variants in MODY genes in 8.1% of EOT1D, occurring in the context of a T1D genetic background. Such genetic variants may contribute to disease precipitation by a β-cell dysfunction mechanism. This supports the concept of different endotypes of T1D, and WES at T1D onset may be a prerequisite for the implementation of precision therapies in children with autoimmune diabetes.